Pseudomonas aeruginosa antibodies in blood spots from patients with cystic fibrosis. Issue 11 (November 1989) - Thanasekaraan, V; Wiseman, M S; Rayner, R J; Hiller, E J; Shale, D J
Abstract : The formation of antibodies to Pseudomonas aeruginosa may be the earliest indicator of pulmonary infection in patients with cystic fibrosis. To enable easy sampling in babies and young children an enzyme linked immunosorbent assay (ELISA) based on a blood spot sample taken on to blotting paper was developed. A sample of approximately 20 microliters of blood was required. A high correlation and level of absolute agreement was shown between paired finger prick and venepuncture blood spots, and between blood spot, serum spot, and serum samples. Healthy controls and non-infected patients with cystic fibrosis had low titres of antibody compared with patients with intermittent and chronic infection. The latter groups had significantly greater antibody titres than normal controls. This assay permits serial measurement of antibodies to P aeruginosa in patients of all ages with cystic fibrosis and may provide a means of assessing the value of such measurements in the detection and management of early infection.